2014
DOI: 10.1371/journal.pone.0087874
|View full text |Cite|
|
Sign up to set email alerts
|

Neonatal Encephalopathic Cerebral Injury in South India Assessed by Perinatal Magnetic Resonance Biomarkers and Early Childhood Neurodevelopmental Outcome

Abstract: Although brain injury after neonatal encephalopathy has been characterised well in high-income countries, little is known about such injury in low- and middle-income countries. Such injury accounts for an estimated 1 million neonatal deaths per year. We used magnetic resonance (MR) biomarkers to characterise perinatal brain injury, and examined early childhood outcomes in South India.MethodsWe recruited consecutive term or near term infants with evidence of perinatal asphyxia and a Thompson encephalopathy scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 43 publications
3
30
0
Order By: Relevance
“…This is similar to findings done in South India where the proportion of newborns with mild HIE was 56% [10] and from another study conducted in Rotunda hospital in Ireland where of the 237 newborn assessed, 65.4% had the mild form of HIE [11]. Of note to practitioners’ majority (98%) of newborns with mild HIE in this study improved and were discharged similar to observations at Muhimbili National Hospital in Tanzania, in Pakistan and India respectively where a total of 92.3% of the newborns were discharged to their mothers [5, 10, 12]. This indicates that with the appropriate care newborns with HIE can improve sufficiently to be discharged early.…”
Section: Discussionsupporting
confidence: 91%
“…This is similar to findings done in South India where the proportion of newborns with mild HIE was 56% [10] and from another study conducted in Rotunda hospital in Ireland where of the 237 newborn assessed, 65.4% had the mild form of HIE [11]. Of note to practitioners’ majority (98%) of newborns with mild HIE in this study improved and were discharged similar to observations at Muhimbili National Hospital in Tanzania, in Pakistan and India respectively where a total of 92.3% of the newborns were discharged to their mothers [5, 10, 12]. This indicates that with the appropriate care newborns with HIE can improve sufficiently to be discharged early.…”
Section: Discussionsupporting
confidence: 91%
“…In a prospective study, Tann et al [29] reported that the prevalence of neonatal bacteremia with a pathogenic organism among encephalopathic infants was 3.5% by blood culture alone, 6.9% by polymerase chain reaction (PCR) alone, and 8.9% by blood culture and PCR in combination. A similar incidence of coexistent bloodstream-positive infection and encephalopathy has been reported from India [30,31]. This is similar to that reported from high-income countries: 8.1% in the ICE trial [32], 6% in NICHD [17], 17% in the TOBY registry [33].…”
Section: Concerns About Perinatal Infectionsupporting
confidence: 87%
“…7, 1113, 19 DuPont et al found that 20% (12/60) of infants with mild NE had an abnormal short-term outcome, including presence of seizures, abnormal neurological examination at discharge, and feeding difficulties beyond the first week of life. Few infants had MRIs in their cohort, nine in total, 66% of which were abnormal.…”
Section: Discussionmentioning
confidence: 99%